Complementary and alternative medicine: Pharmacovigilance in Malaysia and predictors of serious adverse reactions / Sameerah Shaikh Abdul Rahman - Sameerah, Shaikh Abdul Rahman (2019)
In Malaysia, Complementary and Alternative Medicine (CAM) products are readily available and increasingly used. Associated with their use were reports of serious adverse effects. The Centre for Adverse Drug Reaction (ADR) Monitoring, National Pharmaceutical Regulatory Agency (NPRA) through its spontaneous reporting system has received many reports of serious adverse events associated with the use of CAM products. Yet, we know little about factors associated with serious adverse reactions. The study aimed to describe the pattern of spontaneously reported adverse reactions associated with CAM products and identify risk factors associated with serious reactions. We reviewed and analysed all adverse reactions associated with CAM products (including health supplements) submitted to the NPRA between 2000 and 2014. Data analysed and described included patient demography, characteristics and descriptions of adverse reactions, suspected CAM products, severity and outcome of adverse effects. Adverse reactions were considered serious if the reactions led to death, hospitalisation or prolongation of hospitalisation, that were life-threatening, or that caused significant disability. From 74,997 of all reports received by the Centre, 930 (1.2%) involved CAM products. Out of these, 242 (26%) were serious with 36 deaths. Most (78.1%) of the reports implicated unregistered products with 16.7% confirmed to contain adulterants which were mainly dexamethasone. Most of the adverse reaction reports involved Malay users (59.9%), followed by Chinese (32.3%) and they were all mostly adults between the ages of 19-60 (65.2%). Those who experienced adverse effects took CAM iv products mainly for health maintenance and weight loss (61.2%) while the rest used CAM for chronic conditions such as diabetes mellitus, hypertension, stroke, and cancer. The top two most reported adverse events were related to skin and appendages disorders (18.4%) followed by liver and biliary system disorders (13.7%). Binary logistic regression analysis revealed that serious adverse effects were associated with the variables ethnicity, concurrent disease, concurrent drugs taken and use of CAM for a chronic illness. The odds of experiencing serious adverse effects increased if the respondents used CAM products for chronic illnesses compared to those who used CAM for health maintenance [odds ratio (OR) 1.99, 95% confidence interval (CI) 1.46- 2.71], having concurrent disease [OR 1.53, CI 1.05-2.19] and taking concurrent drugs [OR 1.44, CI 1.03-2.02]. Compared to Malay, being of Indian race was associated with decreased odds of experiencing serious adverse effects [OR 0.09, CI 0.01–0.63]. Meanwhile the odds of having serious adverse effects among the race categorised as ‘others’ increased about 2.7 folds compared to Malay [OR 2.64, CI 1.36–5.13]. The findings of this study provide important information on adverse reactions associated with CAM and may help healthcare professionals and the public take necessary measures to ensure its safe use as some products can be life-threatening.